2012
DOI: 10.1038/sc.2012.143
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of a Community Peer Support Service for people with spinal cord injury

Abstract: Study design: Qualitative study involving individual semistructured in-depth interviews. Objectives: To evaluate peer support provided in general hospitals for people with spinal cord injuries (SCIs). Setting: The South West of the United Kingdom. Methods: Fourteen in-depth qualitative interviews were conducted with people with SCI and their close relatives, and with healthcare professionals involved in their care. Transcribed interviews were coded inductively and analysed thematically. Themes were patterned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 22 publications
(33 reference statements)
2
51
0
1
Order By: Relevance
“…Learning from peers has been described as vital in the context of rehabilitation [38] and peer support, along with social support in general, has been shown to be a key factor in the adjustments for living with a SCI [39]. Haas and colleagues [40] determined that the main benefits of a community peer support service for individuals with SCI were the psychological and emotional support by a person with a SCI, advice on living with a SCI, practical advice and information, and ongoing support and friendship. These findings are consistent with those of the current study as well as the findings of other studies in SCI, which have reported the value of non-specific psychological and emotional support through the input of a peer mentor [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Learning from peers has been described as vital in the context of rehabilitation [38] and peer support, along with social support in general, has been shown to be a key factor in the adjustments for living with a SCI [39]. Haas and colleagues [40] determined that the main benefits of a community peer support service for individuals with SCI were the psychological and emotional support by a person with a SCI, advice on living with a SCI, practical advice and information, and ongoing support and friendship. These findings are consistent with those of the current study as well as the findings of other studies in SCI, which have reported the value of non-specific psychological and emotional support through the input of a peer mentor [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Perspective appeared to be separate from spirituality or faith in that the participants' statements did not refer to a higher power or ability to find meaning in their injury from a religious or spiritual standpoint. In addition, while peer support has been shown to promote adjustment to SCI, 18,19 to our knowledge the literature is limited in exploring outcomes associated with being a role model or inspiring others specifically in the SCI community. Further research is warranted to explore these constructs and their relation to an individual's ability to overcome adversity and adapt to SCI.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In this study, peer support seemed to influence those who were making decisions about SPC. It is likely that our participants did not receive adequate information and support when they were asked to consider SPC.…”
Section: Discussionmentioning
confidence: 99%